2018
DOI: 10.1016/j.semcancer.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer genomics and immuno-oncological markers to guide immune therapies

Abstract: There is an increasing awareness of the importance of tumor - immune cell interactions to the evolution and therapy responses of breast cancer (BC). Not surprisingly, numerous studies are currently assessing the clinical value of immune modulation for BC patients. However, till now durable clinical responses are only rarely observed. It is important to realize that BC is a heterogeneous disease comprising several histological and molecular subtypes, which cannot be expected to be equally immunogenic and theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 126 publications
6
104
0
7
Order By: Relevance
“…However, recent studies have challenged this idea and showed that Foxp3+Tregs were associated with improved outcome in BCs (77,78) or bared no impact on OS (79), either regarding the entire group or the HR+ subgroup (43). The present study showed that in the HR-subgroup, higher levels of FOXP3+ Tregs were associated with favorable BCSS, as previously reported (34,35). This finding suggests a subtype-dependent relationship between Tregs and BC prognosis and two possible explanations are offered.…”
Section: Discussionsupporting
confidence: 68%
“…However, recent studies have challenged this idea and showed that Foxp3+Tregs were associated with improved outcome in BCs (77,78) or bared no impact on OS (79), either regarding the entire group or the HR+ subgroup (43). The present study showed that in the HR-subgroup, higher levels of FOXP3+ Tregs were associated with favorable BCSS, as previously reported (34,35). This finding suggests a subtype-dependent relationship between Tregs and BC prognosis and two possible explanations are offered.…”
Section: Discussionsupporting
confidence: 68%
“…When we performed miR‐141‐3p correlation to all mRNAs within both ER‐positive and ER‐negative patients, we also found a strong and significant link to several immune‐related processes (data not shown). These results may indicate that miR‐141‐3p may play a larger role in the ER‐negative subset of patients, in line with a higher frequency of tumor infiltrating lymphocytes in ER‐negative vs. ER‐positive tumors (Hammerl et al , ). Nevertheless, the significant anticorrelation between miR‐141‐3p and CXCL12 ( SDF‐1 ), as well as the latter being a predicted target for this miRNA, does suggest immunological effects from this miRNA in the ER‐positive subset of patients responding to Bev as well.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, it has been revealed that M2 macrophages play a significant role in tumor development. This advocates for the efficient identification of the ITME to discover potential therapeutic targets that may help in the development of new therapies targeting tumor-associated macrophages (Hammerl et al 2018).…”
Section: Comparing Methods Over Simulated Datamentioning
confidence: 99%